Novels of Yusuf Idris: from realism to symbolism - Көптілеуова, Д. Т; Akhmetbekova A. К. (Journal of Oriental Studies, 2018)
The article analyzes the novels of the Egyptian writer Yusuf Idris and features of his realistic method. In the course of the study it turns out that the realism of the writer has notable shades of sentimentalism, romanticism and modernism, which help reveal the content of short stories. It was these shades that determined the periodization of the writer’s work. Studying the reasons for the transition of realism to modernism in novels, the authors of the article connect this with the social themes that the writer touched and the features of the mental stratum of Egyptian society. The realist in his work Yusuf Idris only using symbolism, was able to reflect the consequences of the change in Egypt in the early twentieth century. Thanks to this method, the author of the novels delivered his ideas and code for interpretation.